Simple formulas for pricing and hedging European options in the finite moment log-stable model - Jean-Philippe Aguilar; Jan Korbel (Risks, 2019)
We provide ready-to-use formulas for European options prices, risk sensitivities, and P&L calculations under Lévy-stable models with maximal negative asymmetry. Particular cases, efficiency testing, and some qualitative features of the model are also discussed.
Keywords: 330; stable distributions; Lévy process; option pricing; risk sensitivities; P&L explain